Marked effects of Al-rich AlN transition layers on the performance of CdZnTe films for solar-blind photodetector. (November 2021) - Gu, Jianwen; Shen, Yue; Wen, Dandan; Huang, Jian; Lai, Jianmin; Gu, Feng; Cao, Meng; Wang, Linjun; Min, Jiahua
Abstract: Al-rich AlN transition layers (AlN–Al) on AlN ceramic substrates (c-AlN) are as pioneering work to prepare high quality CdZnTe films. It is pronounced that the structural and electric properties of CdZnTe films based on AlN–Al are enhanced. Among all the CdZnTe films, steepest diminishment of dislocation density can be by 78.84% on the surface and maximal drop is more than quadruple for Cd vacancy on the interface, compared with no Al-rich ones. Subjected to investigation of Al on the interface by EDX and low temperature PL, AlN–Al have provided Al 3+ to compensate defects in CdZnTe films, and the diffusion process of Al 3+ is discussed. The amount of Al 3+ at the interface of CdZnTe is on a tendency of proliferation preceding recession and the optimum is where doping content of Al in transition layers is 1 wt %. The optimal photo-dark current ratio and responsivity of CdZnTe/AlN–Al/c-AlN composites with parallel electrodes under 254 nm UV light illumination are around 369 and 10.6 mA/W, indicating a brilliant prospect of detection in solar-blind region. Highlights: Al-rich films (AlN–Al) is reported and plays a marked role between AlN and CdZnTe films for the first time. AlN–Al can repair Al vacancies and O impurities of the AlN layer sharply. AlN–Al can apply more Al 3+ to compensate Cd vacancies to leave high light response of CdZnTe films.